2010
DOI: 10.1016/j.otohns.2009.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Laryngeal Allograft Survival Using Low‐Dose Everolimus

Abstract: Everolimus successfully prevents laryngeal allograft rejection up to 60 days posttransplantation. It appears to increase the production of regulatory T-cells while decreasing cytotoxic T-cell and dendritic cell response. Everolimus alone or in combination with other immunosuppressants may enable laryngeal transplantation to become a viable reconstructive option following laryngectomy for malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…15 Furthermore, the antitumor properties of everolimus are especially promising for patients who have undergone laryngectomy for cancer. 3 It is notable that in the current study, daily everolimus therapy beginning 180 days after the operation could effectively preserve allografts for an additional 90 days. Although the study showed that daily monotherapy with everolimus did not prevent allograft rejection indefinitely, it suggests that the immunosuppressive effects of everolimus are enhanced after combined pulsing with anti-αβ TCR.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…15 Furthermore, the antitumor properties of everolimus are especially promising for patients who have undergone laryngectomy for cancer. 3 It is notable that in the current study, daily everolimus therapy beginning 180 days after the operation could effectively preserve allografts for an additional 90 days. Although the study showed that daily monotherapy with everolimus did not prevent allograft rejection indefinitely, it suggests that the immunosuppressive effects of everolimus are enhanced after combined pulsing with anti-αβ TCR.…”
Section: Discussionmentioning
confidence: 65%
“…Promising data from our laboratory show that everolimus as a single agent effectively affords long-term allograft survival in mice. 3 Low-dose monotherapy is better tolerated and avoids the side effects commonly observed with additional agents. 15 Furthermore, the antitumor properties of everolimus are especially promising for patients who have undergone laryngectomy for cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the well‐documented risk of cancer recurrence following laryngeal transplantation, everolimus has been studied extensively in murine laryngeal transplant models to evaluate its immunosuppressive and antineoplastic activity. Lott et al showed that everolimus monotherapy successfully prevented laryngeal allograft rejection in mice at 60 days post‐transplantation, and appeared to increase the production of regulatory T cells while decreasing the cytotoxic T‐cell dendritic response, creating a favorable environment for transplantation . Everolimus was then used as a combination therapy in a pulsed‐dose regimen to reduce the total amount of immunosuppression and induce tolerance .…”
Section: Discussionmentioning
confidence: 99%
“…Lott et al showed that everolimus monotherapy successfully prevented laryngeal allograft rejection in mice at 60 days post-transplantation, and appeared to increase the production of regulatory T cells while decreasing the cytotoxic T-cell dendritic response, creating a favorable environment for transplantation. 36 Everolimus was then used as a combination therapy in a pulsed-dose regimen to reduce the total amount of immunosuppression and induce tolerance. 37 Khariwala et al 38 evaluated the effects of irradiation, cyclosporine, combination therapy, pulsed immunosuppression and everolimus on antitumoral activity, showing in a mouse study of squamous cell carcinoma that the use of everolimus resulted in an approximately 50% decrease in local tumor growth, as well as a reduction in distant spread.…”
Section: Discussionmentioning
confidence: 99%